Lung Injury Induced by Antitumor Drugs: Prevalence, Certain Drugs and Their Mechanisms of Action. Part 2 - N. V. Orlova; O. D. Ostroumova; E. V. Shikh; S. V. Smerdin; E. V. Rebrova; V. А. Dyo (Туберкулез и болезни лёгких)
The article analyzes 49 publications on adverse drug reactions occurring during therapy with antitumor drugs. It presents data on pneumotoxicity and its clinical manifestations for such anticancer drugs as bleomycin, busulfan, cyclophosphamide, chlorambucil, methotrexate, nitrosourea derivatives, and taxanes, while the mechanisms of lung injury are not entirely clear and require further research. The prevention of drug-induced lung injury requires raising awareness among practicing physicians of different specialties, primarily general practitioners, rheumatologists, clinical immunologists, pulmonologists, phthisiologists, and oncologists due to non-specific manifestations of drug-induced lung injury and the use of antitumor drugs for other diseases apart from cancer.